Greek Literature: The Basis of the Canon (Minerva, 2019)
This paper discusses the origin and perspectives of the canon of Greek Literature. After outlining the question, both the history of the word κανών and the concept ‘canon’ in Antiquity are explored. Nowadays the existence of different kinds of canon must be assumed: this paper deals with one of them, the so-called internal canon. In order to analyze it, some peculiarities of the ancient Greek Literature must be first identified. Afterwards the study specifies the reasons which make reasonable not to exclude three kinds of authors from the canon: postclassical writers, Christian authors and representatives of transcultural literatures. The paper discusses then the two main points concerning the canon, the textual quality and the importance within the cultural tradition. Finally some considerations concerning the possibility of establishing selective lists of Greek authors on the basis of the comments and critical judgments of ancient readers are proposed.
Keywords: Greek Canon; Greek Literature; Greek Christian Literature; Imperial Greek Literature